Future Prospects for Ascochyta Blight Resistance Breeding in Cool Season Food Legumes - Rubiales, Diego; Fondevilla, Sara (Frontiers in Plant Science, 2012)
Legume cultivation is strongly hampered by the occurrence of ascochyta blights. Strategies of control have been developed but only marginal successes have been achieved. Breeding for disease resistance is regarded the most cost efficient method of control. Significant genetic variation for disease resistance exists in most legume crops with numerous germplasm lines maintained, providing an excellent resource for plant breeders. Fast and reliable screening methods have been adjusted to fulfil breeding programmes needs. However, the complex inheritance controlled quantitatively by multiple genes, have been difficult to manipulate. Successful application of biotechnology to ascochyta blight resistance breeding in legume crops will facilitate both a good biological knowledge of the crops and of the mechanisms underlying resistance. The current focus in applied breeding is leveraging biotechnological tools to develop more and better markers to speed up the delivery of improved cultivars to the farmer. To date, however, progress in marker development and delivery of useful markers has been slow. The limited saturation of the genomic regions bearing putative QTLs in legume crops makes difficult to identify the most tightly-linked markers